Marriage or Freedom? Indonesia's Generation-Z Dilemma in the Midst of Social and Economic Pressure - Andika Ramadhan; Andini Wulan Sukmayanti; Gemilang Adi Perdana; Ovalia Rukmana (Journal of Social Research, 2025)
This study aims to explore Indonesian Generation Z's perceptions of the institution of marriage, identify factors driving marriage postponement, and understand the dynamics of social value change in contemporary society. Using a phenomenological qualitative approach, this research involved 15 participants aged 18-28 from South Jakarta, Bogor, and South Tangerang who were interviewed in-depth with semi-structured guidelines. Data analysis was conducted using NVivo software through open coding, axial coding, and selective coding stages. The results show that Generation Z still regards marriage as a sacred and meaningful institution, but positions it more personally and reflectively as a legal and emotional commitment undertaken consciously. The decision to postpone marriage is influenced by factors of financial readiness, mental and emotional maturity, and alignment of life vision and mission with partners. Meanwhile, social values about marriage have undergone significant shifts from primary life goals to flexible, egalitarian life choices based on self-actualization. Digitization and social media exposure are also found to be factors that strengthen anxiety toward long-term relationships, especially through negative narratives about divorce or unhealthy relationships. These findings align with Maslow's theory of needs, where Generation Z's decisions about marriage reflect the need for financial security, self-esteem, and self-actualization. This study makes an important contribution to enriching qualitative literature on Indonesian youth relationship dynamics, while offering recommendations for BKKBN, Ministry of Youth and Sports, and educational institutions in formulating youth empowerment policies and relationship literacy education.